Young Adult's Response Towards Two Seat Belt Advertisements With Emotional Appeal: Fear-Based And Love-Based Appeals - Tan, Wan Teng (Universiti Malaysia Sarawak (UNIMAS), 2017)
The objective of this study is to explore the response of young adult towards the seat belt advertisements with different emotional appeals. Theory of StimulusOrganism-Response (SOR) was selected to support the response given by the young adult after watching the seat belt advertisement with appeal stimuli. There were two seat belt YouTube videos with fear appeal and love appeal were given to the young adults. Moreover, qualitative method was conducted in this study. There were 24 respondents from different states in Malaysia were tested in this study. The findings of the qualitative study were presented based on respondents' demographics and the responses given by the respondents after watching two seat belt advertisements. The finding shows that young adults prefer the seat belt advertisement with fear appeal approach as they prefer a straightforward message and consequences instead of upbeat and warm advertisement. This study provides a better understanding of the way in which young adults in Malaysia respond to the use of different emotional appeal advertising in seat belt advertisements. Not only that, this study provides useful managerial implication for advertisers in Malaysia.